Juvenile Alewife Passage through a Compact Hydropower Turbine Designed for Fish Safety. (3rd March 2023) - Watson, Sterling M.; Schneider, Abraham D.; Gardner, Lynette C.; Apell, Bryan R.; Thompson, Paige C.; Cadman, Gregor B.; Gagnon, Ian F.; Frese, Chris R.; Wechsler, Jesse F.
Abstract: Hydropower is a valuable renewable energy source, but its effects on the downstream passage of many riverine fish species are not well understood. Turbines that are designed to function as safe downstream passage routes for fish are being developed with the goal of mitigating the effects of hydropower operations on the environment. In this paper, we present the results of a study conducted with the juvenile life stage of the Alewife Alosa pseudoharengus, a major migratory species on the Atlantic coast of North America. The test was conducted at a small hydropower plant located in Freedom, Maine, with a single Restoration Hydro Turbine (RHT) operating under 7.5 m of gross head. Groups of 140–170 fish were released into the intake of a 55‐cm‐diameter RHT and were recaptured with a specialized trap at the turbine discharge outlet. The combined immediate and 48‐h survival rates (±95% CI) for all treatments, corrected for control mortality, were 98.2 ± 2.0% and 100.0 ± 6.6%, respectively. The passage of Alewives through the runner region of the turbine was also captured with high‐speed video. The results of the study demonstrate that the RHT, which is designed for fish safety, is an effective way to pass juvenile alosines downstream at hydropower facilities.